Socialization to Science: Using Media to Help Young People in the United States Consider a Career in a STEM-related Field. Issue 4 (4th July 2021) - Levine, Kenneth J.; Miller, Vernon D.; Quilliam, Elizabeth Taylor; McAlister, Anna R.; Aley, Melinda R.
ABSTRACT: Vocational anticipatory socialization (VAS) is a multi-year, multi-step process that begins in childhood and informs young adults about possibilities for their future work-life experience. This manuscript describes two field experiments that examine media as a VAS socialization source through an investigation of the impact of a televised STEM program geared to elementary school children between the ages of 8 and 14. Additionally, the gender of the television host was manipulated to examine the effect of host gender on increasing interest in STEM. A pretest/posttest design measured attitudes and interest changes in STEM and STEM careers following media viewing. The findings demonstrate that media acts as a socialization agent and can increase a child's interest in STEM. Parental influence and gender differences are also discussed.